Legal Analysis of the Role of the Regional Assembly in the Monitoring of Notaries After Amendment of Law No. 2/2014 - Riyanti, Devi; Susilo, Adhi Budi; Aziz, Ahmad Shamsul Abd (Walisongo Law Review (Walrev), 2023)
Notaris, a specialized position appointed by the state, must adhere to the law in its activities. An institution is responsible for implementing and overseeing notaries in a specific region (district/city) to ensure that notaries do not violate their duties. Thus, establishing a Regional Supervisory Council is essential to act as the vanguard in conducting guidance and supervision of notaries. The research methodology employed is juridical-empirical, with a descriptive analysis specification. The findings reveal that the role of the Regional Supervisory Council in guiding and overseeing notaries in Semarang Regency is based on Ministerial Regulations and decisions, and its actions are grounded in the Notary Law, specifically Article 70 of Law No. 2 of 2014, an amendment to Law No. 30 of 2004 concerning the Position of Notary Public. Challenges faced by the Regional Supervisory Council for Notaries in executing its authority are twofold. Internally, there are constraints related to minimal budgeting, limited supporting facilities, and the busy schedules of each official. Externally, challenges include several notaries lacking permanent offices, the coexistence of signboards for Land Deed Officials with notaries, which should be separate, and the disorganized arrangement of notarial protocols.Notaris merupakan jabatan khusus dari negara dituntut untuk tunduk pada undang-undang dalam kegiatannya, terdapat suatu badan yang mempunyai kewenangan dan kewajiban dalam melaksanakan dan pengawasan notaris di daerah (Kabupaten/kota) agar notaris tidak melakukan pelanggaran dalam menjalankan tugas jabatanya maka perlu adanya Majelis Pengawas Daerah sebagai garda depan dalam melaksanakan Pembinaan dan Pengawasan terhadap notaris Metode dalam penelitian ini adalah yuridis empiris, spesifikasi yang digunakan bersifat deskritif analisis (1). Hasilnya, peran Majelis Pengawas Daerah dalam pembinaan dan pengawasan notaris di wilayah Kabupaten Semarang dalam menjalankan tugas mengacu pada Peraturan Menteri, keputusan menteri dan untuk dasar tindakannya mengacu pada undang-undang jabatan notaris pada Pasal 70 Undang-Undang No 2 Tahun 2014 perubahan atas Undang-Undang No 30 Tahun 2004 Tentang Jabatan Notaris Kendala yang di hadapi oleh Majelis Pengawas Daerah Notaris dalam melaksanakan kewenangannya. bersifat intern meliputi: anggaran yang minim, sarana penunjang yang terbatas dan kesibukan masing-masing pengurus. lalu yang bersifat ekstern adalah beberapa Notaris yang belum mempunyai kantor tetap,Masih terdapat papan nama Pejabat Pembuat Akta Tanah (PPAT) dengan Notaris, yang seharusnya tandanya dipisah dan protokol notaris yang tidak tertata rapi